2016
DOI: 10.1111/tri.12660
|View full text |Cite
|
Sign up to set email alerts
|

Nature, timing, and severity of complications from ultrasound-guided percutaneous renal transplant biopsy

Abstract: Summary We sought to review our kidney transplant biopsy experience to assess the incidence, type, presenting symptoms, and timing of renal transplant biopsy complications, as well as determine any modifiable risk factors for postbiopsy complications. This is an observational analysis of patients at the University of Wisconsin between January 1, 2000, and December 31, 2009. Patients with an INR ≥1.5 or platelet counts less than 50 000 were not biopsied. An 18‐gauge needle was used for biopsy. Over the study pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
69
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 25 publications
7
69
2
1
Order By: Relevance
“…Another similar study of kidney allograft biopsies [25] showed 1.8% of complications, mostly comprising mild complications (0.7%) and only 0.19% life-threatening complications. The difference in the study was that it comprised all allograft biopsies from the institution in- Data is presented as number (percentage), mean ± SD, range.…”
Section: Discussionmentioning
confidence: 99%
“…Another similar study of kidney allograft biopsies [25] showed 1.8% of complications, mostly comprising mild complications (0.7%) and only 0.19% life-threatening complications. The difference in the study was that it comprised all allograft biopsies from the institution in- Data is presented as number (percentage), mean ± SD, range.…”
Section: Discussionmentioning
confidence: 99%
“…By use of Doppler ultrasound, 12 AVF were detected (4.6%) neither of which required embolization. Our complication rates can be compared to historical data in Table 1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Sample adequacy could be retrospectively assessed for 156 tissue core samples.…”
mentioning
confidence: 99%
“…Specifically it is necessary to instruct the patient about the possible nature of the difficulties and the necessity to immediately contact the respective hospital, if signs of complications occur. This approach could also be applied in the case of a biopsy of transplanted kidney, where a number of late serious bleeding episodes at a time interval up to 2 days after surgery have been reported [9] .…”
Section: Discussionmentioning
confidence: 99%